ANALYZING THE USE OF B35 BIODIESEL ON THE DISTANCE AND FUEL FILTERS LIFETIMES FOR LOCOMOTIVES CC201 AND CC203 - Atmaja, Dadang Sanjaya; Damayanti, Ajeng Tyas; Utomo, Ilham Satrio; Prasetya, Henry Widya; Firjatullah, Aisha Aristawidya (Politeknik Perkeretaapian Indonesia Madiun, 2025)
Blends of biodiesel, like B35, are becoming more and more popular as the demand for cleaner energy sources grows. There are a number of difficulties with using biodiesel, particularly with respect to diesel engine fuel filtration systems. The purpose of this study is to determine the fuel filter's level of contamination at particular mileage intervals, assess how well the filter works with biodiesel blends, and calculate the fuel filter's lifespan when using B35 biodiesel. The authors have conducted an experimental study involving a testing apparatus to measure the flow rate at the filter. Real-time data on fuel flow rate and filter cloggi ng rate will be collected and analyzed to determine the impact of filter efficiency on fuel changes. The experimental data will be compared and contrasted to draw meaningful conclusions about the correlation between filter clogging and fuel flow rate. The data shows that the CC201 filter experiences less contamination compared to the CC203 filter. These results suggest that the CC201 maintains better performance at the distances tested. Filter quality was estimated based on the remaining flow rate capacity, showing a direct correlation between mileage and filter deterioration. Firstly, it was found that the level of contamination experienced by the CC201 fuel filter was superior to that of the CC203 filter. Secondly, the relationship between fuel filter life and locomotive mileage is illustrated by a scatter plot graph showing a decreasing trend line. Thirdly, from the use of B35 fuel, the performance of the fuel filter decreased at a percentage of 10% and 13% on each locomotive.